The synergistic effect between phages and Ceftolozane/Tazobactam in Pseudomonas aeruginosa endotracheal tube biofilm - Viviane de C. Oliveira; Alba Soler-Comas; Amanda C.S.D. Rocha; Cláudia H. Silva-Lovato; Evandro Watanabe; Antoni Torres; Laia Fernández-Barat (Emerging Microbes and Infections, 2024)
Although an increased effectiveness has been suggested when phages and antibiotics are combined, this approach has not been tested against a mature biofilm on an endotracheal tube (ETT) surface. This study evaluated the effect of short- and long-term combined phage-antibiotic therapy in a control of a mature biofilm on an ETT surface. Pseudomonas aeruginosa strains, including susceptible and resistant clinical samples, were used to develop the ETT biofilm. Biofilm was treated with 108PFU/mL of phage_2, phage_18 or 5 μg/mL of ceftolozane/tazobactam, alone or in combination with phages. The sequential combination of the two different phages and ceftolozane/tazobactam was also tested. Biofilm viability was assessed after short (2, 4, 24 h) and long-(48, 72 h) term treatment exposure using colony forming unit measurement. For long-term exposition, a new treatment shot was added every 24 h. In the sequential combination, the phage type was switched at 24 h of treatment. Regarding the susceptible strains, the treatments had limited antibiofilm effect after 2, 4 and 24 h. After 48 and 72 h, administering phages alone had no effect on biofilm viability, indicating the emergence of phage-resistant phenotypes. Nonetheless, the combined phage-antibiotic treatment reduced the biofilm viability in about 5-log, whilst antibiotic alone reduced in about 3-log. The sequential combination of phages and antibiotic reduced the biofilm viability in about 6-log. With respect to the resistant strains, no antibiofilm activity was observed regarding the treatment arms. The combination of phages and ceftolozane/tazobactam showed a synergism strain-dependent, being more apparent in susceptible strains.